Clinical outcomes and gut microbiota analysis of severe alcohol-associated hepatitis patients undergoing healthy donor fecal transplant or pentoxifylline therapy: single-center experience from Kerala. (5th December 2022) - Philips, Cyriac Abby; Ahamed, Rizwan; Rajesh, Sasidharan; Singh, Shobhit; Tharakan, Ajit; Abduljaleel, Jinsha K; Augustine, Philip
Abstract: Background: Severe alcohol-associated hepatitis (SAH) patients with infections have a high short-term mortality rate. Gut microbiota dysbiosis plays an important role in the pathogenesis of SAH. Preliminary studies have demonstrated long-term benefits with healthy donor fecal microbiota transplantation (FMT). Data on FMT compared with pentoxifylline for SAH and relevant gut microbial changes are lacking in literature. Methods: From January 2019 to February 2021, retrospective analysis of a single hospital's records revealed 47 SAH patients undergoing FMT (100 mL/day via nasoduodenal tube for 7 days) and 25 matched patients receiving pentoxifylline (400 mg/8 h for 28 days). The primary end point was a 6-month survival rate. Secondary end points included incidence of ascites, hepatic encephalopathy, infections, acute kidney injury, and gut microbiota changes between post-therapy groups. Biomarker discovery and network analysis were also performed to identify significant taxa of gut microbiota in post-treatment groups in retrospectively stored stool samples. Results: All were males. The 6-month survival rate was higher in the patients undergoing FMT than in patients receiving pentoxifylline (83.0% vs 56.0%, P  =   0.012). At the end of 6-month follow-up, the incidences of clinically significant ascites (56.0% vs 25.5%, P  =   0.011), hepatic encephalopathy (40.0% vs 10.6%, P  =   0.003), and critical infections (52.0% vs 14.9%, P  <   0.001) in patients administered pentoxifylline were significantly higher than those in patients treated with FMT. At 3 months, biomarker analysis revealed a significant abundance of Bifidobacterium and Eggerthella in the FMT group and the pentoxifylline group, respectively. At 6 months, Bifidobacterium in the FMT group and pathogenic Aerococcaceae in the pentoxifylline group were notable. Network analysis showed beneficial taxa ( Bifidobacterium ) as a central influencer in those undergoing FMT at 6 months. Conclusions: Healthy donor FMT improved survival rate and reduced liver-related complications compared with pentoxifylline. These clinical benefits were associated with favorable modulation of intestinal bacterial communities. Difficult-to-treat SAH patients may be safely bridged to transplantation using FMT. Controlled trials evaluating long-term outcomes are an unmet need.